Anastomotic Leaks following Esophagectomy for Esophageal and Gastroesophageal Junction Cancer: The Key Is the Multidisciplinary Management - Ortigão,Raquel (2023)
Abstract Introduction: Anastomotic leakage after esophagectomy is associated with high mortality and impaired quality of life. Aim: The objective of this work was to determine the effec-tiveness of management of esophageal anastomotic leakage (EAL) after esophagectomy for esophageal and gastro-esophageal junction (GEJ) cancer. Methods: Patients submitted to esophagectomy for esophageal and GEJ cancer at a tertiary oncology hospital between 2014 and 2019 (n = 119) were retrospectively reviewed and EAL risk factors and its management outcomes determined. Results: Older age and nodal disease were identified as independent risk factors for anastomotic leak (adjusted OR 1.06, 95% CI 1.00-1.13, and adjusted OR 4.89, 95% CI 1.09-21.8). Patients with EAL spent more days in the intensive care unit (ICU; median 14 vs. 4 days) and had higher 30-day mortality (15 vs. 2%) and higher in-hospital mortality (35 vs. 4%). The first treatment option was surgical in 13 patients, endoscopic in 10, and conservative in 3. No significant differences were noticeable between these patients, but sepsis and large leakages were tendentially managed by surgery. At follow-up, 3 patients in the surgery group (23%) and 9 in the endoscopic group (90%) were discharged under an oral diet (p = 0.001). The in-hospital mortality rate was 38% in the surgical group, 33% in the conservative group, and 10% in endoscopic group (p = 0.132). In patients with EAL, the presence of septic shock at leak diagnosis was the only predictor of mortality (p = 0.004). ICU length-of-stay was non-significantly lower in the endoscopic therapy group (median 4 days, vs. 16 days in the surgical group, p = 0.212). Conclusion: Risk factors for EAL may help change pre-procedural optimization. The results of this study suggest including an endoscopic approach for EAL.